Identification of aberrant subvesical bile duct by using intraoperative fluorescent cholangiography: A case report. (2019) - Iwasaki, Toshimitsu; Takeyama, Yoshifumi; Yoshida, Yuta; Kawaguchi, Kohei; Matsumoto, Masataka; Murase, Takaaki; Kamei, Keiko; Takebe, Atsushi; Matsumoto, Ippei; Nakai, Takuya
Highlights: Aberrant subvesical bile duct poses risk of bile duct injury during cholecystectomy. Intraoperative fluorescent cholangiography (IFC) could allow us to identify a fine minute bile duct. IFC is one of a promising technique to improve the safety of cholecystectomy further. Abstract: Introduction: Aberrant subvesical bile ducts are rare structural anomaly located in the peri-hepatic gallbladder fossa. This duct poses the risk for intraoperative bile duct injury resulting in clinically relevant bile leakage. Presentation of case: Aberrant subvesical bile duct was detected by preoperative magnetic resonance cholangiopancreatography in a 52-year old woman with gallbladder polypoid tumor harboring the risk to be gallbladder cancer. During open cholecystectomy with full thickness dissection, the aberrant duct was identified by intraoperative fluorescent cholangiography (IFC), and dissected safely. Discussion: Aberrant subvesical bile ducts are mostly found unexpectedly as intra and/or postoperative bile leakage, and remain an important cause of bile duct injuries after laparoscopic cholecystectomy. IFC, which offers real-time imaging of biliary anatomy, has a potential to overcome these problems. Conclusion: We performed cholecystectomy by using IFC to identify the aberrant subvesical bile duct. To the best of our knowledge, this is the first report showing the fluorescence image of an aberrant subvesical bile duct in a state of nature.